The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18203/2394-6040.ijcmph20183085
|View full text |Cite
|
Sign up to set email alerts
|

A study on menstrual hygiene practices and problems amongst adolescent girls in Udaipur, Rajasthan, 2018

Abstract: Background: Adolescence in girls has been recognized as a special period in life cycle. This period is marked with onset of menarche. It is linked with several perceptions and practices, which sometimes results in adverse health outcomes. So, this study was carried out to assess practices of menstruation in adolescent girls, to find out its related problems and socio-cultural beliefs.Methods: A cross sectional study was carried out during January-February 2018 in two schools of Udaipur using convenient samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…Our finding is in agreement with studies done by Palak et al, 2017 and Tundia et al, 2018 who have reported that religious restrictions were present in 91.59% and 88.3% of the menstruating girls respectively. 12,13 However, in contrast to our finding a study done by Alam et al, showed that only 51% of the menstruating girls were not allowed to perform religious activities. 14…”
Section: Discussioncontrasting
confidence: 84%
“…Our finding is in agreement with studies done by Palak et al, 2017 and Tundia et al, 2018 who have reported that religious restrictions were present in 91.59% and 88.3% of the menstruating girls respectively. 12,13 However, in contrast to our finding a study done by Alam et al, showed that only 51% of the menstruating girls were not allowed to perform religious activities. 14…”
Section: Discussioncontrasting
confidence: 84%
“…Change of sanitary pad should be frequent to avoid severe infection at genital area among the girls and also washing of hands with Soap should be practiced. [1][2][3][4][5][6][7] In rural area many of the girls were suffering from restrictions of their family members. Such as attending religious functions, touching stored food, playing outside, sleeping on routine bed etc.…”
Section: Introductionmentioning
confidence: 99%
“…Inanother study it was found that 75% wrap in paper/polythene bag and dispose [12]. In this study, 60.6% used to clean genitalia during menstruation with soap-water where as in another study 66.54% girls were using water to clean genitals during menstruation [15]. Remedial measures adopted during menstruation were taking adequate rest (44%), seeking medical advice if needed (22.9%), and drinking plenty of fluid (13.8%) in the present study.…”
Section: Discussionmentioning
confidence: 54%